An experience with colistin applied in treatment of imunocompromised patients with peritonitis on peritoneal dialysis - Djurdjević Mirković, Tatjana; Gvozdenović, Ljiljana; Majstorović-Stražmešter, Gordana; Knežević, Violeta; Ćelić, Dejan; Mirković, Siniša; Popović, Milica (Vojnosanitetski pregled, 2015)
Introduction. Immunocompromised patients, such as those with multiple myeloma on peritoneal dialysis, are particularly susceptible to the occurrence of peritonitis. Case report. We presented a 56-year-old female patient with a 10-year history of multiple myeloma. The patient was on peritoneal dialysis since 2010. During 2012 the patient had the first episode of peritonitis that was successfully managed, but in 2013 the second episode of peritonitis occured. Analysis of dialysate culture and exit site swab revealed the presence of multiresistant Acinetobacter spp., which was susceptible only to colistin. Prompt colistin therapy was administered at the doses of 100,000 units/day during six days, which resulted in complete recovery of the patient, as well as improvement of local abdominal findings. Gram-negative bacteria (genus Acinetobacter) are common causative agents in hospital-acquired infections. Studies confirmed susceptibility of Acinetobacter to colistin, which was also the case with the presented patient. Intravenous administration of colistin resulted in a complete remission of this severe, life-threatening peritonitis. Conclusion. Patients with multiple myeloma and renal failure are highly prone to severe life-threatening infections.
Keywords: multiple myeloma; peritoneal dialysis; peritonitis; colistin